Analysis of Limb Muscle Power of Male and Female Basketball Athletes KONI Madiun City Year 2024 - Ardyansyah, Ardyansyah Arief Budi Utomo; Titin, Titin Kuntum Mandalawati; Agung, Agung Dwi Darmawan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The Madiun City has a myriad of athletes, in this case basketball athletes. Both male athletes and female athletes are all mentored and trained. The purpose of this study was to find scientific data on the leg muscle power of male and female basketball athletes at KONI Madiun City. This research method uses quantitative methods with an experimental approach with a one shoot model design. The target of this study involved 10 male athletes and 10 female athletes. The test instrument used is the Vertical Jump Test. The results showed that the power produced by male basketball athletes showed a minimum power of 301 Joules, and a maximum power of 429 Joules with an average power of 365.47 Joules. While the power produced by female basketball athletes shows a minimum power of 169 Joules, and a maximum power of 255 Joules with an average power of 206.51 Joules. With the conclusion, in Men's Basketball Athletes there are 1 person in the excellent category, 8 people in the good category, and 1 person in the moderate category. Meanwhile, in Female Basketball Athletes, there are 1 person with a good category, 5 people with a moderate category, and 4 people with a less category.